Integrative Governance in Transformation of Islamic Education Management in The Digital Era - Moh. Baqir; Abd. Muhith; Zainal Abidin; Sadiq Ibrahim Mijinyawa (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to analyze the transformation of Islamic education management based on integrative governance in the digital era. The study focuses on three main aspects: strengthening integrative governance and leadership, digitalizing management and learning systems, and developing quality assurance, curriculum, and Islamic character. This research employed a qualitative approach with a descriptive-analytical case study design. Data were collected through in-depth interviews, observation, and document analysis, and were analyzed using thematic analysis. The findings indicate that the transformation of Islamic education management takes place through the strengthening of participatory leadership, the use of digital technology in administration and learning, and the development of a curriculum that integrates Islamic values, digital literacy, and contemporary educational needs. However, the transformation still faces several challenges, including limited human resource competence, uneven technology utilization, weak data integration in decision-making, and the suboptimal implementation of quality assurance systems based on Islamic character. This study concludes that the transformation of Islamic education management cannot be achieved merely through technical digitalization; rather, it requires integrative governance that continuously connects leadership, technology, quality assurance, curriculum, and Islamic values. These findings contribute to the development of Islamic education management studies, particularly in formulating adaptive, participatory, and contextually relevant governance models for the digital era.